2016
DOI: 10.4172/2155-9864.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life of Patients with Sickle Cell Disease

Abstract: Objective: The aim of the present study was to evaluate the health-related quality of life in pediatric patients with Sickle Cell Disease. Methods:An analytical cross-sectional study was performed. Pediatric patients suffering from Sickle Cell Disease below the age of 21 were compared with asymptomatic pediatric individuals. Clinical and demographic data were collected along with the Pediatric Quality of Life Inventory (PedsQL 4.0). Results:The sample was composed of 68 children and adolescents in the "Sickle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…This study assessed the HRQoL of SCD patients in two tertiary care hospitals in the Asir Region of Saudi Arabia using the SF‐36. The participants had low scores for the eight subscales of the HRQoL items, which is consistent with previous studies on SCD patients 3,14,17‐19 . We found that gender affects the physical functioning score, as the female patients in our study exhibited better physical scores than the male patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study assessed the HRQoL of SCD patients in two tertiary care hospitals in the Asir Region of Saudi Arabia using the SF‐36. The participants had low scores for the eight subscales of the HRQoL items, which is consistent with previous studies on SCD patients 3,14,17‐19 . We found that gender affects the physical functioning score, as the female patients in our study exhibited better physical scores than the male patients.…”
Section: Discussionsupporting
confidence: 92%
“…The participants had low scores for the eight subscales of the HRQoL items, which is consistent with previous studies on SCD patients. 3,14,[17][18][19] We found that gender affects the physical functioning score, as the female patients in our study exhibited better physical scores than the male patients. This result conflicts with Ahmed et al's study conducted in Makka, Saudi Arabia, which suggests no significant difference between genders in the physical score of SCD patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation